The influence of renewable energy and economic freedom aspects on ecological sustainability in the G7 countries. (14th September 2022) - Alola, Andrew Adewale; Doganalp, Nihat; Obekpa, Hephzibah Onyeje
Abstract: With the exemption of Canada, the G‐7 countries have largely flourished at the detriment of their ecological sustainability bearing in mind that these countries' have remained ecologically deficit for several decades. Given the potential effect of environmental degradation associated with the trend of ecological deficit of these countries, this study attempts to understand the contribution of renewable energy dimensions through the measure of renewable energy efficiency and renewable energy use alongside evaluating the role of the four main aspects of economic freedom. By using empirical tools, the findings revealed that renewable energy aspects contribute to environmental sustainability among the countries through a significant mitigation of their ecological footprint. Importantly, the aspects of economic freedom, that is, government size, legal system and property rights, freedom to trade internationally, and regulation hampers environmental sustainability by increasing the countries ecological footprint. The elasticity of impact of this dimension of economic freedom is in the range of 0.19–0.21 at 1% statistically significant level. However, population of these countries does not show a detrimental effect, rather the finding revealed that population improves environmental quality by a statistically significant degree. Given these revelations, there are deducible policy take home from this study.